(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
The research was carried out at PP Tiley, Morotai Island Regency, North Maluku Province, from April to May 2024. Field data was collected for 1 week, namely on 10 - 17 May 2024. Tiley fishing port was chosen as the research location because this location was wrong. a fishing port which is often used as a fishing base and landing place for caught fish in Morotai Island Regency. This research uses the case method. The research results show that the utilization level of the ice factory is not yet optimal, while the utilization rate of ABF and cold storage has exceeded the optimal limit. The strategy for developing cold chain facilities at PP Tiley, Morotai Island Regency, includes: (1) Improving the quality of cold chain facility services at PP Tiley, Morotai Island Regency; (2) Collaborating with the private sector in the construction of air blast freezer and cool storage facilities at PP Tiley, Morotai Island Regency; (3) Development of an integrated cold chain; and (4) Additional logistics transportation trips for distribution of catches from PP Tiley, Morotai Island Regency to consumers.